RAFT/MADIX emulsion copolymerization of vinyl acetate and N-vinylcaprolactam: towards waterborne physically crosslinked thermoresponsive particles. Issue 14 (24th March 2017) - Etchenausia, Laura; Khoukh, Abdel; Deniau Lejeune, Elise; Save, Maud
Abstract : Controlled radical emulsion polymerization as a tool to synthesize thermoresponsive PVCL-based amphiphilic copolymer particles crosslinked by supramolecular hydrophobic interactions. Abstract : Well-defined poly( N -vinylcaprolactam- co -vinyl acetate) thermoresponsive particles physically crosslinked by means of hydrophobic interactions were synthesized by polymerization-induced self-assembly. It was highlighted that a xanthate-terminated poly(ethylene glycol) (PEG-X) efficiently acted as both a stabilizer and a macromolecular chain transfer agent for the RAFT/MADIX batch emulsion copolymerization of N -vinylcaprolactam (VCL) and vinyl acetate (VAc), enabling the direct synthesis in aqueous dispersed media of PEG- b -P(VAc- co -VCL) block copolymers. It was emphasized that a fraction of 47 mol% of hydrophobic VAc in the second block of the copolymer was suitable for maintaining the integrity of the self-assembled PEG- b -P(VAc- co -VCL) block copolymer particles at low temperature while exhibiting a temperature-induced phase transition. The well-defined physically crosslinked particles interestingly behaved as thermoresponsive colloids analogous to chemically crosslinked microgels. The PEG- b -P(VAc0.47 - co -VCL0.53 ) particles were able to undergo a reversible swollen-to-collapse transition with increasing temperature in the absence of hysteresis. The PEG- b -P(VAc0.17 - co -VCL0.83 ) block copolymer with a lower fraction of VAc in the copolymer (17 mol%) behaved oppositely as very small objects were present in the aqueous phase at low temperature ( T < 20 °C) and self-assembled into large aggregates by increasing the temperature. Finally, the statistical copolymers based on VAc and VCL were successfully hydrolyzed into promising thermoresponsive biocompatible statistical copolymers based on vinyl alcohol and N -vinylcaprolactam co-monomer units.